UTILIZATION OF INFORMATION TECHNOLOGY AND INTERNAL CONTROL SYSTEMS ON ACCOUNTABILITY OF PROCUREMENT OF GOODS AND GOVERNMENT SERVICES - Zulfaidah Zulfaidah; Irmah Halimah Bachtiar; Nursyam Nursyam (Business and Entrepreneurial Review, 2020)
This study aims to determine the effect of the use of information technology and internal control systems on the accountability of government procurement of goods and services. This study uses a type of causality research with a quantitative approach. Data obtained from surveys through the distribution of questionnaires with a total sample of 60 originating from implementers in the Electronic Procurement Services Section, Selection Committee, Procurement Officers, Commitment Making Officers, Providers (partners). Data is processed using SPSS statistical analysis tools. The results showed that partially the utilization of Information Technology and Internal Control Systems had a positive and significant effect on the Accountability of Procurement of Goods and Services of the Regional Government of Pangkajene and Kepulauan Regency.Keywords: Accountability for Procurement of Goods and Services, Internal Control Systems, Information Technology.